2011
DOI: 10.1128/iai.00782-10
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin Contributes to Neuronal Damage in Experimental Bacterial Meningitis

Abstract: Thrombopoietin (Tpo), which primarily regulates megakaryopoiesis, and its receptor (c-Mpl) are expressed in the brain, where Tpo exhibits proapototic effects on neurons. In the present study, we investigated the implication of Tpo in experimental pneumococcal meningitis. Following intrathecal infection with the encapsulated Streptococcus pneumoniae strain D39, we observed upregulation of Tpo mRNA expression at 12 h and 24 h in brain homogenates of wild-type C57BL/6 mice. c-Mpl mRNA expression was upregulated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…We have also shown that Thpo is produced in the osteoblastic niche and that Mpl + HSCs reside closely to osteoblasts . Mature hematopoietic cells, such as macrophages, have also been reported as a source of Thpo production . Within the BM, we reported that mature megakaryocytes may produce Thpo and function as a niche .…”
Section: Regulation Of Thpo Production and Mpl Expression For Hsc Maisupporting
confidence: 52%
See 1 more Smart Citation
“…We have also shown that Thpo is produced in the osteoblastic niche and that Mpl + HSCs reside closely to osteoblasts . Mature hematopoietic cells, such as macrophages, have also been reported as a source of Thpo production . Within the BM, we reported that mature megakaryocytes may produce Thpo and function as a niche .…”
Section: Regulation Of Thpo Production and Mpl Expression For Hsc Maisupporting
confidence: 52%
“…31 Mature hematopoietic cells, such as macrophages, have also been reported as a source of Thpo production. 58 Within the BM, we reported that mature megakaryocytes may produce Thpo and function as a niche. 59 Both studies identified Thpo expression in osteoblasts and megakaryocytes using quantitative PCR and antibody detection.…”
Section: Regulation Of Thpo Production and Mpl Expression For Hsc Maimentioning
confidence: 99%
“…In the animal models of E. coli meningitis, apoptosis of neurons was present in the dentate gyrus of the hippocampus 20 . Evidence from experimental meningitis caused by other CNS-infecting pathogens, such as Streptococcus pneumoniae 17 , 21 23 and group B Streptococcus 18 , 24 indicated that apoptosis is a major contributor to neuronal cell death. The molecular mechanism of neuronal apoptosis in bacterial meningitis remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MAP kinase pathways are activated, which potentiate maturation. Finally, less well studied but equally important, are the antiapoptotic pathways that are activated [25][26][27]. As discussed next, TPO binding results in mitosis, endomitosis, maturation, and a wide variety of anti-apoptotic effects in megakaryocyte precursors and in megakaryocytes [6,28].…”
Section: Thrombopoietin Functionmentioning
confidence: 99%